Seed analysis of Lupinus albescens Hook. & Arn. - Paim, Luciana Pinto; Avrella, Eduarda Demari; Luchesse, Júlio; de Freitas, Elisete Maria; Lazarotto, Marília; Fior, Claudimar Sidnei (Iheringia, Série Botânica., 2019)
The objective of this study was to describe the dispersion, color, size and morphological characteristics of fruits and seeds of Lupinus albescens, as well as pre-germinative treatments, aspects of luminosity and seed conservation. Above twenty populations were collected in São Francisco de Assis/RS and Alegrete/RS, pre-germinative treatments (seven pre-germinative methods, scarification times and temperatures) were analyzed; photoblastic test (seeds scarified between sandpapers, submitted to 25ºC); imbibition curve (control and scarification treatments between sandpapers); seeds conservation (cold room in plastic bag and natural environment in paper bag). Evaluations: description of fruits, seeds and viability analysis, using a completely randomized design. The results showed dispersion by autocoria, brown coloration of fruits and seeds and some striped seeds. Superior pre-germinative treatment was between sandpapers, for 40 seconds and under 25ºC. Seeds are classified as neutral photoblasts and without dormancy. Natural environment and paper bag were suitable for storage.